Protective effects of folic acid on ischemia‒reperfusion injury in rat uterus: reduces inflammation damage and apoptotic death - Zahid Paksoy; Nihat Yumusak (BMC Veterinary Research)
Abstract Background Uterine torsion is a pregnancy pathology that poses risks to both maternal and fetal health. This condition is closely associated with the relaxation of uterine ligaments due to hormonal changes and the increased size of the gravid uterus. It occurs when the uterus rotates around its own axis. This torsion can result in ischemia, and if untreated, may progress to necrosis and fetal loss. Folic acid has protective effects against oxidative stress, inflammation, and apoptosis. The aim of this study was to investigate the potential of folic acid to reduce ischemia‒reperfusion (IR) injury in the rat uterus. Results IR caused severe edema, inflammation, congestion, hemorrhage, vasoconstriction, and necrosis in the uterus. Histopathological damage was less pronounced in rats treated with folic acid. Although the endometrial layer, critical for fertility, suffered significant damage, folic acid effectively prevented this injury. Immunohistochemical analysis revealed that caspase-3 activity, a marker of apoptosis, increased in response to IR. However, folic acid treatment attenuated this activity, and uterine inflammation also reduced. High-dose folic acid inhibited TNF-alpha immunoreactivity. Interestingly, folic acid did not activate antioxidant mechanisms to reduce oxidative stress. Nevertheless, it mitigated IR-induced damage by reducing endometrial injury and preventing inflammation and apoptosis. Conclusions As a result, uterine torsion can lead to endometrial damage, degeneration, inflammation, and apoptosis, potentially affecting fertility. High-dose folic acid treatment may protect the uterus from these damages, thereby preserving fertility. This study suggests that folic acid, particularly at high doses, may be safe and beneficial treatment to prevent IR damage and promote uterine health.